PENERAPAN MODEL MAKE A MATCH DALAM PEMBELAJARAN FIKIH UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA KELAS III MIN 20 ACEH BESAR - Azhar Azhar (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
In finding the problem of jurispruding learning in class III-1 MIN 20 Aceh Besar and found that jurispruded teachers have not developed much learning model in teaching. Teachers use lecture methods, Q&A, discussions, have not used learning models, so students are less instrumental and motivated in learning. This learning condition causes students to be less enthusiastic about taking lessons, at the time of learning students sit more, listen, take notes and work on exercise problems. The author tries to apply a learning model that is considered suitable to activate students and will get the completion of student learning, namely the make a match model. The implementation of this make a match model by way of students looking for a pair of problem cards that match the answer card held by the student. Based on the research that has been carried out, it can be concluded that the completion of student learning in grades II-1 MIN 20 Aceh Besar in jurispruded subjects increased from a value of 71.42 (cycle I) to 92.85 (cycle II). Teacher activity increased from a grade of 90.71 (cycle I) to 94.44 (cycle II). Student activity also increased from a grade of 83.33 (cycle I) to 91.66 (cycle II). Thus there is an increase in the completion of student learning through the application of make a match model in jurispruding subjects in grades III-1 MIN 20 Aceh Besar.